Polystyrene nanoplastics induce oxidative stress in Aurelia coerulea polyps, microglia, and mice - Song, Mingshuai; Wei, Zhenyu; Wang, Jingqiang; Li, Liangzhi; Li, Xiangyu; Ma, Xiaofen; Pozzolini, Marina; Liu, Xinyan; Xiao, Liang; Zhong, Ping (Frontiers in Immunology, 2025)
IntroductionThis study investigates the oxidative stress responses induced by polystyrene nanoplastics (PS-NPs) across three distinct biological models—Aurelia coerulea polyps, BV2 microglial cells, and ICR (Institute of Cancer Research) mice. We aimed to explore the involvement of the mitogen-activated protein kinase (MAPK) signaling pathway as a potential mechanism in invertebrate and cellular systems, while evaluating neurobehavioral outcomes in vivo.MethodsOxidative stress markers including catalase (CAT), total antioxidant capacity (T-AOC), and malondialdehyde (MDA) were quantified in all the three models. Transcriptomic analysis and RT-qPCR validation targeting the MAPK signaling pathway were performed in Aurelia coerulea polyps and BV2 microglial cells. Behavioral assessments, including the open field test and novel object recognition test, were conducted in mice to evaluate anxiety-like behavior and cognitive impairment following PS-NPs exposure.ResultsIn polyps, PS-NPs exposure resulted in shortened tentacle length and a dose-dependent decrease in T-AOC and CAT activity, along with an increase in MDA levels, indicating oxidative stress. BV2 microglia exhibited intracellular PS-NP accumulation, increased reactive oxygen species (ROS), upregulated inflammatory cytokines, and elevated apoptosis. Transcriptome analysis revealed significant activation of the MAPK signaling pathway in both polyps and BV2 cells. In mice, PS-NPs caused reduced central zone exploration and lower discrimination index scores, consistent with anxiety-like behavior and cognitive dysfunction. Immunohistochemical staining revealed microglial activation in the hippocampus, exhibiting the neurotoxic effects of PS-NPs.DiscussionWhile these models represent distinct organisms and biological contexts, all demonstrated consistent oxidative stress responses upon PS-NPs exposure. Although we do not claim direct equivalency across species, the converging evidence from marine, cellular, and mammalian systems highlights the widespread biological risks posed by nanoplastics. These findings provide a foundation for evaluating environmental and public health threats associated with PS-NPs.